1974
DOI: 10.3171/jns.1974.41.1.0063
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformations, aneurysms, and pregnancy

Abstract: ✓ The authors report a retrospective study of 146 patients to assess the extent to which aneurysms, arteriovenous malformations, and pregnancy interact. The natural history of the lesions was modified if the women became pregnant. Clinical syndromes, diagnosis, neurosurgical and obstetrical management, and treatment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1
17

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(114 citation statements)
references
References 10 publications
3
93
1
17
Order By: Relevance
“…In what concerns the delivery, despite what had been previously reported 13 , there is no evidence that normal delivery is associated with an increased bleeding risk in pregnant women with intact AVM. Horton et al believe that delivery in a patient with AVM, which was not surgically excised, can be performed either vaginally or by cesarean section 3,9,14. On the other hand, there are no studies comparing delivery modes in pregnant women with AVM rupture (ICH), but in the few cases reported the option was to perform cesarean sections 10,14 .…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In what concerns the delivery, despite what had been previously reported 13 , there is no evidence that normal delivery is associated with an increased bleeding risk in pregnant women with intact AVM. Horton et al believe that delivery in a patient with AVM, which was not surgically excised, can be performed either vaginally or by cesarean section 3,9,14. On the other hand, there are no studies comparing delivery modes in pregnant women with AVM rupture (ICH), but in the few cases reported the option was to perform cesarean sections 10,14 .…”
Section: Discussioncontrasting
confidence: 42%
“…In 1974, Robinson et al, 13 evaluating 24 cases, concluded that a woman who has had AVM would have 87% chance of developing ICH during pregnancy. On the other hand, Horton et al 9 in 1990, in a study of 451 women of childbearing age with AVM, concluded that pregnancy does not increase the risk of bleeding of an AVM, estimating it at 3.5% (risk of bleeding in the non pregnant female population of childbearing age, with an AVM, estimated at 3.1%).…”
Section: Discussionmentioning
confidence: 99%
“…1,[25][26][27][28][29][30][31][32][33][34] It was initially thought that there was a significant risk of bleeding associated with rapid changes in cardiac output in any woman with CAVMs, for example, during the first trimester, labor, and delivery, but a retrospective analysis of 451 women found that the 3.5% risk of primary hemorrhage from a CAVM of any etiology during pregnancy did not differ significantly from the annual bleeding rate in a non-gravid patient. 29,31 No relationship with parity or trimester has been found. 35 In the event of any CAVM rupture during pregnancy, the risk of recurrent bleeding is unknown, but estimates have been as high as 27-30%, particularly during labor, delivery, and subsequent deliveries.…”
Section: Cerebral Avmsmentioning
confidence: 99%
“…32 There are descriptions in the literature of the successful treatment of both ruptured and unruptured CAVMs of varying etiologies during pregnancy that were subsequently followed by successful delivery at term. 25,[31][32][33][34] Spinal AVMs Spinal AVMs (SAVMs) affect up to 1% of patients with HHT. 5 Rupture of SAVMs is uncommon, and most patients present with a gradual onset of symptoms ranging from neck or back pain, to nerve root pain, to focal sensory and motor neurology, to disturbance of defecation and micturition.…”
Section: Cerebral Avmsmentioning
confidence: 99%
See 1 more Smart Citation